Management of Bhagandara W.S.R to complicated fistula-in-ano: A case report (Indian Journal of Case Reports, 2019)
Bhagandara (Fistula-in-ano) is a disease which occurs in the region of anal canal described in Ayurveda literature. It is an infective condition of the anal canal usually caused by crypto glandular infection of anal crypts. There is an abnormal communication between two epithelial surfaces and track is lined by unhealthy granulation tissue. The present case study was conducted on a male patient aged 85-years-old suffering from the disease for last one and half year. Patient came to us recurrence after incision and drainage of perianal abscess. K?arasutra therapy using IFTAK (Interception of fistulous tract with the application of Kh?arasutra) technique of treatment was adopted. The daily dressing was done with jatyaditaila. The patient was cured completely within 8 weeks of treatment. There was no side effect or any complication after regular follow up of 2 months. The treatment technique was proved to be a very effective and convective treatment option.